Morphological, anatomical and isozyme variability among taro (Colocasia esculenta) accessions from southeastern part of Central Java, Indonesia - ARI PITOYO; ANGELIA ARUM PRAMETA; MARSUSI MARSUSI; SURATMAN SURATMAN; SURANTO SURANTO (Biodiversitas Journal of Biological Diversity, 2018)
Pitoyo A, Prameta AA, Marsusi, Suratman, Suranto. 2018. Morphological, anatomical and isozyme variability among taro (Colocasia esculenta) accessions from southeastern part of Central Java, Indonesia. Biodiversitas 19: 1811-1819. The objective of this study was to evaluate morphological, anatomical and isozyme variability among taro accessions from southeastern part of Central Java (Indonesia). A total of 20 taro accessions were collected from a wide range of sites during field surveys. Morphological characters measurements were taken on vegetative structures such as roots, stems, leaves, and corms. Anatomical characters were observed from both paradermal and transverse sections of leaf. Identification of biochemical markers was done by using peroxidase and esterase isozyme system. A UPGMA dendrogram among accessions was constructed based on the genetic similarity matrix by applying a cluster analysis using a computer programme, NTSYS Version 2.00. The analysis of variance for morphological and anatomical characters revealed that there was significant difference for majority of the tested traits indicating that there was a variability among the taro accessions. Polymorphism was observed using isozymes of esterase (12 banding pattern) and peroxidase (8 banding pattern). Based on the dendrogram at a level of 62 % similarity, taro accessions were segregated into two major clusters. In Cluster I, the closest relationship was shown between SKH and SKA accessions that had 96 % coefficient of similarity. The ten accessions from Klaten, Sragen, and Karanganyar were then clustered separately as Cluster II with coefficient of similarity 73.52 %.